Dampak pembangunan Flora Wisata Santerra De Laponte bagi lalu lintas - Lestari, Widya Dwi (Maliki Interdisciplinary Journal, 2024)
The development of Flora Wisata Santerra de Laponte in Malang Raya has had a significant impact on the surrounding traffic conditions. This study aims to analyze these impacts through primary and secondary data collection. Primary data was obtained through field surveys and interviews with local residents and visitors, while secondary data came from traffic reports and development planning documents.The results show that there is a significant increase in vehicle volume, especially during weekends and holiday seasons, which causes congestion at several main access points to tourist sites. Inadequate road infrastructure also worsens traffic conditions. This congestion and increase in vehicle volume has led to complaints from the local community and reduced the comfort and safety of road users. This study concludes that infrastructure improvements and better traffic management are needed to overcome the negative impacts of the increase in the number of vehicles due to the development of Flora Tourism Santerra de Laponte. Recommendations include increasing road capacity, implementing a technology-based traffic management system, and cooperation between the tourism management and local government. These measures are expected to reduce the negative impact on traffic and improve convenience for visitors and the local community.